2018
DOI: 10.1007/s13300-018-0462-9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of BHG and PPHG to Overall Hyperglycemia in T2DM Patients Treated with LM25 and LM50: Post Hoc Analysis of a Randomized Crossover Trial

Abstract: IntroductionTo investigate the relative contribution rates of basal hyperglycemia (BHG) and postprandial hyperglycemia (PPHG) to overall hyperglycemia in patients with type 2 diabetes mellitus (T2DM) treated with insulin lispro mix 25 and 50 (LM25 and LM50) as evaluated by continuous glucose monitoring (CGM).MethodsEighty-one T2DM patients treated with premixed human insulin 70/30 (PHI70/30) were randomly divided into two groups and received a crossover protocol. In the first 16-week stage, one group received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…These studies also revealed that BG plays a major role in the subgroup of patients with HbA1c levels > 8.5%, and the relative contribution of PPG decreased with increasing HbA1c (from 65.5% to 39.2%). The difference in the relative contribution of PPG between the studies performed by Li et al 20 and Riddle’s et al 7 may be that Riddle et al used 5.6 mmol/L as a baseline, whereas Li et al used 6.1 mmol/L as a baseline, leading to the overestimation of the relative contribution of PPG. The NGT curve considers physiological fluctuations in normal people after meals, and thus, can be used as a baseline to evaluate the relative contribution of PPG and BG to hyperglycaemia.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…These studies also revealed that BG plays a major role in the subgroup of patients with HbA1c levels > 8.5%, and the relative contribution of PPG decreased with increasing HbA1c (from 65.5% to 39.2%). The difference in the relative contribution of PPG between the studies performed by Li et al 20 and Riddle’s et al 7 may be that Riddle et al used 5.6 mmol/L as a baseline, whereas Li et al used 6.1 mmol/L as a baseline, leading to the overestimation of the relative contribution of PPG. The NGT curve considers physiological fluctuations in normal people after meals, and thus, can be used as a baseline to evaluate the relative contribution of PPG and BG to hyperglycaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies of diabetes patients being administered insulin [20][21][22] and Glucagon like peptide-1 receptor agonists (GLP-1 RAs) 23 are a good complement to our research. These studies also revealed that BG plays a major role in the subgroup of patients with HbA1c levels > 8.5%, and the relative contribution of PPG decreased with increasing HbA1c (from 65.5% to 39.2%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations